STRUKTUR DAN KOMPOSISI VEGETASI POHON DI STASIUN PENELITIAN HUTAN BRON DESA WAREMBUNGAN KABUPATEN MINAHASA - Stenly B. Melalolin; Marthen T. Lasut; Johny S. Tasirin; Reynold P. Kainde (Universitas Sam Ratulangi, 2016)
ABSTRACT This research was conducted in Bron Research Center in the village of Warembungan, regency of Minahasa, during the months of September, October and November 2015. This research aims to know the structure and composition of tree vegetation with trunk diameters above 20 cm at Bron Research Center. The method used was random plot, where plots were randomly placed within the 50-hectare research location. There were 5 observation plots, each 100x100m large and covering a total area of 5 hectares. Observations collected data on the species and number of individuals for each species in each of the plots. The data was analyzed using three parameters: density and relative density, frequency and relative frequency dominance and relative dominance, and Important Value Index (IVI). Results show that the species with the highest IVI was Palaquium obovatum 66,43%, with 13,2 individuals/ha, and the lowest IVI was Caryota mitis 1.97%, with 0,2 individuals/ha. Keywords: Structure and composition, IVI.